Storing Lesion-free Tooth Morphology for Biomorphic Dental Restoration Design - Pingting Lin; Yang Jiao; Yanping Pei; Jihua Chen (International Journal of Personalized Medicine, 2017)
The goal of dental restoration is to restore and reconstruct the function, integrity, and morphology of missing tooth structures. At present, dental crowns are usually fabricated by referencing the homonym and adjacent teeth to design the morphology of the restoration, followed by empirical modifications on the restoration morphology. The original morphology of an intact natural tooth, if available, would allow for a balance of the horizontal and vertical forces generated by the surrounding tissues. Otherwise, it is hard for a restoration to reproduce the original tooth morphology. Discrepancies between original tooth morphology and restorations, such as axial over-contour or inappropriate occlusion, may break physiologically established balance, causing patient discomfort or even malocclusion and occlusal diseases. Therefore, to design and fabricate dental restorations with the original tooth morphology could be of great value to oral health. Literature indicates that physiological changes in tooth morphology slowly progress throughout one’s life. We present a hypothetical biomorphic dental restoration design that records the intact tooth morphology of a patient before lesions occur to allow for future design and fabricate of dental restorations. Using a copy of the pre-existing tooth abutment for restoration could result in none or fewer adjustments needed for restoration, and harmony with the surrounding tissues.
Keywords: Computer-Aided Design